On Interval Valued Fuzzy Bi-interior Ideals in Semigroups (European Journal of Pure and Applied Mathematics, 2023)
In this paper, we study the concept of an interval valued fuzzy bi-interior ideal. We investigate the properties of an interval valued fuzzy bi-interior ideal in semigroups. We characterize a regular semigroup in terms of an interval valued fuzzy bi-interior ideal.
Keywords: bi-interior ideals, interval valued fuzzy bi-interior ideals